Nickel cobaltite@nanocarbon hybrid materials as efficient cathode catalyst for oxygen reduction in microbial fuel cells - Xia, Wei-Yan; Tan, Liang; Li, Nan; Li, Jie-Cheng; Lai, Shao-Hao (Journal of materials science, 2017)
The high efficiency of cathode catalyst used in the oxygen reduction reaction is a vital factor guaranteeing for the microbial fuel cells (MFCs). In this work, two novel nickel cobaltite@nanocarbon hybrids were rationally designed and successfully prepared as efficient cathode catalysts in air–cathode MFCs. Impressively, the achieved maximum power density of the MFCs equipped with NiCo 2 O 4 @MWCNTs cathode was about 356 mW m −2 , which is significantly higher than that of the MFCs with other cathodic catalysts. This work may provide not only the fundamental studies on nanocarbon-supported mixed-valent transition-metal oxides but also a new kind of promising alternative electrode in the technology of power generation from MFCs.